Roger Fry: Art and Life - Christopher Reed (Cahiers Victoriens et Edouardiens)
This piece presents, in their totality, two little-known texts by Roger Fry: one an exercise in emotional self-analysis and the other a rumination on mosquitos. These essays are analyzed to consider Fry’s application of formalist aesthetics to the problems of life.